Structural changes induced by ultrasound during aging of the boehmite phase - Domingos, Roberto N. [UNESP]; Vollet, Dimas R. [UNESP]; Bucalon, Antonio J. [UNESP] (Elsevier, 1997)
Structural changes induced by ultrasound during the aging of the aluminum monohydroxide (boehmite) were studied by means of X-ray diffraction (XRD) and nitrogen adsorption. The BET surface area and the pore volume of the ultrasound stimulated hydroxide (HU) are about 40% less than those of the non-stimulated one (HS). The mean pore size practically does not change, while the mean crystallite size (L) is about 25% greater in the HU system. The increase of L alone is not enough to account for the surface area diminution, suggesting that the sonication also induces compaction by elimination of some porosity. The sonication of the precursor hydroxide does not seem to play an apparent role in the structural properties of the resulting calcinated γ-alumina. © 1997 Elsevier Science B.V.
Keywords: γ-alumina; Boehmite; Porous structure; Absorption; Aging of materials; Alumina; Nitrogen; Porosity; Surface structure; X ray diffraction analysis; Ultrasound stimulated hydroxide; Ultrasonic effects